PENGELOMPOKAN WILAYAH CURAH HUJAN KALIMANTAN BARAT BERBASIS METODE WARD DAN FUZZY CLUSTERING - Ina Junaeni; Dewi Yuliani; Risana Ayahbi; - Noersomadi; - Nurzaman; Teguh Hardjana (Lembaga Penerbangan dan Antariksa Nasional, 2010)
In order to decrease the climate information gap, the rainfall clustering based on the TRMM data is presented. Then, the rainfall pattern could be determined for all region. Using the principal component analysis as the interface, clustering analysis, namely the Ward and the Fuzzy Clustering methods, the rainfall in West Kalimantan could be grouped in to four clusters according to its homogenity. The first cluster consists of grids that gather in the Karimata strait, Java Sea, and some area in West Kalimantan Lands. The second group was built by grids in the land with homogeneous topography. The third group in the middle of West Kalimantan was a cluster in the land which has different elevation. The fourth group was a cluster in the northern Kalimantan and close to the South China Sea. The West Kalimantan rainfall derived from the TRMM data has the equatorial and monsoonal patterns. The monsoonal pattern was exhibited by the cluster in the ocean (first cluster), and the equatorial pattern was showed by clusters in the land (second, third, and fourth clusters). The equatorial rainfall pattern revealed that the first wet month occuring in April, whereas the second wet month occured in December or January. The month with lowest rainfall is August. Key word: Rainfall pattern, Rainfall cluster, Ward and Fuzzy Clustering methods